La représentation sociale de la santé des entraîneurs de hockey sur glace au Québec - Guicherd-Callin, L. B.; Otis, J.; Potvin, L. (Movement & Sport Sciences - Science & Motricité, 2018)
The hockey coach is an actor who can intervene in health promotion actions. Its involvement in this type of action will be conditional on the social representation of this group on what health is. The purpose of the article is to document the ice hockey coaches social representation (SR) of health, documented and exploited as part of a process of knowledge legitimization with Hockey Québec. The methodology is based on a data triangulation obtained by a questionnaire and individual interviews. A sample of 330 people answered the questionnaire and at this number, 12 coaches participated in the interviews. Categorical and prototypical analyzes were performed on word combinations from the questionnaire as well as a thematic analysis for the interviews. The study highlights the structure of the RS with three conceptions and six-dimensions. It gives elements to judge the opportunities and limitations to involve ice hockey coaches in health promotion. This study offers a new contribution to the debate on the structure of social representations.